The study of TV reception from the perspective of organized citizenship - Rosique Cedillo, Gloria (Historia y Comunicación Social, 2014)
Considering the present audiovisual context convergent with new technologies and the new role of the media users, it is important to determine to what extent the organized media users affect or can get to influence in the development of the television. This question begins to become in an inherent necessity in the field of the media investigation in the relation “society-mass media”, regarding to the paradigm of the new communication multidirectional model. Therefore, this article proposes to carry out a bibliographical revision in the most important Spanish databases in the communication area, with the aim of identify the amount of scientific production developed in the field of television reception, from the perspective of organized citizens and their impact on television.
Keywords: Citizens; TV Viewers; Theory; TV Reception; Social Capital.